2016
DOI: 10.4238/gmr.15028002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an alfalfa (Medicago sativa L.) peroxidase gene in transgenic Arabidopsis thaliana enhances resistance to NaCl and H2O2

Abstract: ABSTRACT. Peroxidases (PODs) are enzymes that play important roles in catalyzing the reduction of H 2 O 2 and the oxidation of various substrates. They function in many different and important biological processes, such as defense mechanisms, immune responses, and pathogeny. The POD genes have been cloned and identified in many plants, but their function in alfalfa (Medicago sativa L.) is not known, to date. Based on the POD gene sequence (GenBank accession No. L36157.1), we cloned the POD gene in alfalfa, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Overexpression of SOD gene increase SOD activity in rubber tree leaves, and activated all ROS scavenging enzymes (Leclercq et al 2012). Plant transgenic-POD was significantly higher tolerance to H2O2 than wild-type plant (Teng et al 2016). The high concentration and activity of antioxidant enzymes in the plant tissue were proved enhancing tolerance to stress such as over-exploitation.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of SOD gene increase SOD activity in rubber tree leaves, and activated all ROS scavenging enzymes (Leclercq et al 2012). Plant transgenic-POD was significantly higher tolerance to H2O2 than wild-type plant (Teng et al 2016). The high concentration and activity of antioxidant enzymes in the plant tissue were proved enhancing tolerance to stress such as over-exploitation.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed that the overexpression of transcription factor (TF) genes (i.e., MxbHLH18 and MxWRKY53) [23,24], antioxidant enzyme genes (i.e., AhCuZnSOD and AtAPX3) [25,26], osmotic regulation genes (i.e., MdHXK1 and AtBAG6) [27,28] and ion transporter genes (i.e., OsNHX7 and CNGC1) [29,30] changed salinity tolerance in transgenic plants. In alfalfa, several genes that participate in the salinity stress response, such as MsCBL4 [31], MsPP2CA1 [32] and MsPOD [33] have also been reported.…”
mentioning
confidence: 99%